Antimicrobial potential of pyroligneous extracts – a systematic review and technological prospecting - Souza, Juliana Leitzke Santos de (Braz J Microbiol, 2018)
Pyroligneous extract is applied in diverse areas as an antioxidant, an antimicrobial, and an anti-inflammatory agent. The discovery of new cost-effective antimicrobial agents of natural origin remains a challenge for the scientific community. This study aimed to conduct a systematic review and a technological forecasting of the existent evidence regarding the use of pyroligneous extract as a potential antimicrobial agent. Studies were identified through an investigation of various electronic databases: PubMed, SciFinder, Web of Science, Scopus, Scielo, Google scholar, and ProQuest. Patents were searched through INPI, Google patents, Espacenet, Patents online, USPTO, and WIPO. The literature on antimicrobial activity of pyroligneous extract are limited given the short duration of studies and variability in study design, use of pyroligneous preparations, and reports on results. However, evidence suggests the potential of pyroligneous extract as a natural antimicrobial agent. The most studied activity was the role of PE as a food preservative. However, pyroligneous extracts are also effective against pathogenic bacteria in the oral microflora and treatment of candidal infections. Further research is needed using standardized preparations of pyroligneous extracts to determine their long-term effectiveness and ability as antimicrobial agents.